2010
DOI: 10.1073/pnas.0913721107
|View full text |Cite
|
Sign up to set email alerts
|

Potential on-shore and off-shore reservoirs for CO 2 sequestration in Central Atlantic magmatic province basalts

Abstract: Identifying locations for secure sequestration of CO 2 in geological formations is one of our most pressing global scientific problems. Injection into basalt formations provides unique and significant advantages over other potential geological storage options, including large potential storage volumes and permanent fixation of carbon by mineralization. The Central Atlantic Magmatic Province basalt flows along the eastern seaboard of the United States may provide large and secure storage reservoirs both onshore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…Carbon dioxide capture and storage (CCS) is a major component of a portfolio of advanced energy technologies required to mediate the rise in concentration of atmospheric CO 2 . In particular, sequestration of CO 2 as geochemically stable solid carbonates of Ca, Mg, and Fe through reaction with basaltic rocks has been tendered as a possible permanent sink for CO 2 (Seifritz, 1990;McGrail et al, 2006;Alfredsson et al, 2008;Oelkers et al, 2008;Gislason et al, 2009;Goldberg et al, 2009;Shikazono et al, 2009;Schaef et al, 2010). Immense basalt provinces exist worldwide in: Iceland, Hawaii, the Columbia River Plateau and India's Deccan Volcanic Province (McGrail et al, 2006;Prasad et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide capture and storage (CCS) is a major component of a portfolio of advanced energy technologies required to mediate the rise in concentration of atmospheric CO 2 . In particular, sequestration of CO 2 as geochemically stable solid carbonates of Ca, Mg, and Fe through reaction with basaltic rocks has been tendered as a possible permanent sink for CO 2 (Seifritz, 1990;McGrail et al, 2006;Alfredsson et al, 2008;Oelkers et al, 2008;Gislason et al, 2009;Goldberg et al, 2009;Shikazono et al, 2009;Schaef et al, 2010). Immense basalt provinces exist worldwide in: Iceland, Hawaii, the Columbia River Plateau and India's Deccan Volcanic Province (McGrail et al, 2006;Prasad et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although oil and gas reservoirs (Kovscek 2002;Bachu and Shaw 2003;Hovorka et al 2009;Esposito et al 2010;Zhang et al 2011) and unmineable coal seams (White et al 2005;Faiz et al 2007a;Kronimus et al 2008a) formations have been identified as potential geologic repositories for CO 2 , deep (often saline) nonpotable aquifers are preferred and are the most widely studied. Reasons include ubiquity, availability of mature technology, high storage capacities, and the potential for CO 2 conversion to carbonate minerals (Bachu and Adams 2003;Goldberg et al 2008Goldberg et al , 2010McGrail et al 2006). Estimates for CO 2 storage capacity in single, deep nonpotable aquifers range from 10 -2 to 10 4 Gt (Herzog 2001;McGrail et al 2006;Goldberg et al 2008;Gislason et al 2010;Donda et al 2011;Medina et al 2011) and would be sufficient for storing decades to centuries of future CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Deccan Traps in central and western India have an estimated storage capacity of 150 Gt CO 2 (Jayaraman, 2007). Similarly, the storage capacity of the Columbia River Basalt Group in the northwestern United States has been estimated to be on the order of 100 Gt CO 2 (McGrail et al, 2006), and offshore basalt formations within the Juan de Fuca plate and Central Atlantic magmatic province hold potential for CO 2 disposal on comparable scales (Goldberg et al, 2008(Goldberg et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%